2017
DOI: 10.1111/obr.12541
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐loss interventions and gut microbiota changes in overweight and obese patients: a systematic review

Abstract: Imbalances in the gut microbiota, the bacteria that inhabit the intestines, are central to the pathogenesis of obesity. This systematic review assesses the association between the gut microbiota and weight loss in overweight/obese adults and its potential manipulation as a target for treating obesity. This review identified 43 studies using the keywords 'overweight' or 'obesity' and 'microbiota' and related terms; among these studies, 17 used dietary interventions, 11 used bariatric surgery and 15 used microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
136
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 91 publications
(267 reference statements)
10
136
1
10
Order By: Relevance
“…From a recent meta-analysis, bariatric surgery-and associated physiologic and metabolic changes-significantly reduced all-cause mortality from cancer (~33%-60%). [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131] Retrospective studies found bariatric surgery significantly reduced risk for preand postmenopausal BC as well as skin cancer (including melanoma). 123,132 Of note for subtype-specific BC, bariatric surgery led to a 64% reduced risk in premenopausal ER tumors like TNBC.…”
Section: Tnbcs Also Disproportionately Affect African American Andmentioning
confidence: 99%
“…From a recent meta-analysis, bariatric surgery-and associated physiologic and metabolic changes-significantly reduced all-cause mortality from cancer (~33%-60%). [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131] Retrospective studies found bariatric surgery significantly reduced risk for preand postmenopausal BC as well as skin cancer (including melanoma). 123,132 Of note for subtype-specific BC, bariatric surgery led to a 64% reduced risk in premenopausal ER tumors like TNBC.…”
Section: Tnbcs Also Disproportionately Affect African American Andmentioning
confidence: 99%
“…Calorie restriction increases the microbiota richness and diversity that is correlated with nutrient deficiency rather than weight loss [10]. Calorie restrictive diets generally reduce the butyrate-producing bacteria such as Firmicutes, Lactobacillus, and Bifidobacterium species [39]. The changes in gut microbiota resulting from calorie restriction are similar to those induced by bariatric surgery in experimental animals and humans [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Calorie restrictive diets generally reduce the butyrate-producing bacteria such as Firmicutes, Lactobacillus, and Bifidobacterium species [39]. The changes in gut microbiota resulting from calorie restriction are similar to those induced by bariatric surgery in experimental animals and humans [39,40]. Calorie restriction and bariatric surgery modulate bile acid metabolism to increase circulating bile acid concentrations and reduced the secondary bile acid production.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that gut microbiota dysbiosis would lead to a number of diseases, including gastrointestinal disorders [2,[33][34][35], obesity [36][37][38], cardiovascular diseases [39][40][41], allergy [42][43][44] and CNS-related diseases [30,45], which affect a large population in the world. Besides, mood and behaviour are also susceptible to alterations in the gut microbiota [3].…”
Section: Gut Bacteria and Diseasesmentioning
confidence: 99%